Checkpoint inhibitors in the treatment of urological malignancies - Popovic, Lazar S (ESMO Open, 2017)
Checkpoint inhibitors are monoclonal antibodies attach to several different receptors on T-cells or tumour cells expressing receptors for cytotoxic T-lymphocyte antigen 4 (CTLA-4), programmed death-1 (PD-1) and their ligand (PD-L1). Since 2010, numerous trials on different tumour types have been conducted, which was resulted in these drugs being approved for the treatment of melanoma, lung cancer, Hodgkin's lymphoma and head and neck cancers. Urological cancers, especially urothelial and renal-cell carcinomas, are immunogenic tumours. Since the late 70s, the bacillus Calmette-Gurin (BCG) vaccine has been used for intravesical instillation in non-muscle invasive bladder cancer from the mid-90s up until the discovery of tyrosine kinase inhibitors (TKIs) in 2007, interleukin-2 (IL-2) and interferon alpha (IFNα), which were the standard of care for metastatic renal-cell cancer. Two checkpoint inhibitors are already approved by the Food and Drug Administration: atezolizumab for metastatic urothelial cancer and nivolumab for metastatic renal-cell carcinoma. There are many drugs are in different phases of clinical development. Here we review the current status of checkpoint inhibitors in the treatment of urological tumours.